Statins: pros and cons - Pinal-Fernandez, Iago (Med Clin (Barc), 2017)
Statins inhibit the critical step of cholesterol synthesis in which 3-hydroxy-3-methylglutaryl coenzyme A (HMGC) is transformed to mevalonate by the enzyme HMGC reductase. By doing so, they have a potent lipid-lowering effect that reduces cardiovascular risk and decreases mortality. Since the mevalonate pathway also influences endothelial function, the inflammatory response, and coagulation, the effects of statins reach well beyond their cholesterol lowering properties. As with all drugs, statins may have adverse effects; these include musculoskeletal symptoms, increased risk of diabetes, and higher rates of hemorrhagic stroke. However, the frequency of adverse effects is extremely low and, in selected patient populations, the benefits of statins considerably outweigh the potential risks.